Cardioprotective Effect of Chronic Hypoxia Involves Inhibition of Mitochondrial Permeability Transition Pore Opening - Alanova, P; Alan, L; Neckar, J; Ostadal, B; Kolar, F (Physiological research, 2024)
The aim of the study was to examine the potential role of mitochondrial permeability transition pore (mPTP) in the cardioprotective effect of chronic continuous hypoxia (CH) against acute myocardial ischemia/reperfusion (I/R) injury. Adult male Wistar rats were adapted to CH for 3 weeks, while their controls were kept under normoxic conditions. Subsequently, they were subjected to I/R insult while being administered with mPTP inhibitor, cyclosporin A (CsA). Infarct size and incidence of ischemic and reperfusion arrhythmias were determined. Our results showed that adaptation to CH as well as CsA administration reduced myocardial infarct size in comparison to the corresponding control groups. However, administration of CsA did not amplify the beneficial effect of CH, suggesting that inhibition of mPTP opening contributes to the protective character of CH.
Keywords: transportní proteiny mitochondriální membrány; Mitochondrial Permeability Transition Pore; přechodový pór mitochondriální permeability; Mitochondria, Heart; Chronic Disease; reperfuzní poškození myokardu; krysa rodu Rattus; srdeční mitochondrie; Hypoxia; Myocardial Reperfusion Injury; zvířata; infarkt myokardu; potkani Wistar; hypoxie; cyklosporin; Rats, Wistar; Male; chronická nemoc; Myocardial Infarction; Rats; Cyclosporine; Animals; Mitochondrial Membrane Transport Proteins; mužské pohlaví